STED with wavelengths closer to the emission maximum - Vicidomini, Giuseppe; Hell, Stefan (Optics express, 2012)
In stimulated emission depletion (STED) nanoscopy the wavelength of the STED beam is usually tuned towards the red tail of the emission maximum of the fluorophore. Shifting the STED wavelength closer to the emission peak, i.e. towards the blue region, favorably increases the stimulated emission cross-section. However, this blue-shifting also increases the probability to excite fluorophores that have remained in their ground state, compromising the image contrast. Here we present a method to exploit the higher STED efficiency of blue-shifted STED beams while maintaining the contrast in the image. The method is exemplified by imaging immunolabeled features in mammalian cells with an up to 3-fold increased STED efficiency compared to that encountered in standard STED nanoscopy implementations.
Gesehen am 05.11.2018